2012
DOI: 10.1007/s11239-012-0827-2
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with quercetin and 3′,4′-dihydroxyflavonol inhibits platelet function and reduces thrombus formation in vivo

Abstract: Flavonols are polyphenolic compounds with reported cardiovascular benefits and have been shown to exhibit antiplatelet properties in vitro. While some studies have shown inhibition of platelet aggregation following dietary supplementation with flavonol rich foods, few studies have assessed the ability of flavonols to inhibit platelet mediated thrombus generation in vivo. Furthermore, the duration of benefit and the influence of different dosing regimens remain unclear. In this study we investigate the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…In ApoE deficient mice, a diet supplemented with Mulberry leaves (1%) reduced atherosclerotic lesions in the aorta by 40% as well as demonstrating a lag time in the onset of LDL oxidation [181]. Quercetin is also anti-atherosclerotic by inhibiting platelet aggregation [182]. In bovine aortic endothelial cells, treatment with mulberry leave extract inhibited the TNFα mediated activation of NFκB thereby repressing the inflammatory response, as well inhibiting the expression of LOX-1 [183].…”
Section: Bioactive Components Of Polyphenol Rich Foodsmentioning
confidence: 99%
“…In ApoE deficient mice, a diet supplemented with Mulberry leaves (1%) reduced atherosclerotic lesions in the aorta by 40% as well as demonstrating a lag time in the onset of LDL oxidation [181]. Quercetin is also anti-atherosclerotic by inhibiting platelet aggregation [182]. In bovine aortic endothelial cells, treatment with mulberry leave extract inhibited the TNFα mediated activation of NFκB thereby repressing the inflammatory response, as well inhibiting the expression of LOX-1 [183].…”
Section: Bioactive Components Of Polyphenol Rich Foodsmentioning
confidence: 99%
“…The preparation of human platelets and aggregation assays were performed using standard protocols as described by us previously 15, 16 . Briefly, human blood was collected in 3.2% citrate containing vacutainers via venepuncture from healthy, aspirin-free individuals with informed consent in accordance with the methods approved by the University of Reading Research Ethics Committee.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals who consume diets with low levels of saturated fatty acids together with a substantial amount of fruits and vegetables have been shown to have reduced development of CVD risks 13, 14 . In particular, a number of dietary flavonoids such as quercetin 15 , tangeretin 16 , nobiletin 17 , luteolin and apigenin have been shown to exhibit inhibitory effects in platelets by modulating diverse signalling cascades 18 . However, several challenges are associated with using dietary components for the prevention and treatment of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…30 In brief, PRP aggregation was performed in the presence of 100 µg/mL fibrinogen and 1 mM CaCl 2 at 37°C with constant stirring (1000 r/min). Platelet aggregation baseline was set against murine PPP diluted 1:2 in RCD buffer pH 7.4.…”
Section: Platelet Aggregationmentioning
confidence: 99%
“…29 Furthermore, we showed that the administration of Que or DiOHF at 6 mg/kg for seven consecutive days inhibits platelet function and reduces thrombus formation in a mouse model of plateletmediated arterial thrombosis. 30 Therefore, the aim of this study was to investigate the effects of Que or DiOHF on in vivo arterial thrombus formation in animal models with diabetes and study the effects on platelet function ex vivo.…”
Section: Introductionmentioning
confidence: 99%